SELECTION OF GARBAGE TRUCKS WITH RATIONAL PARAMETERS ACCORDING TO THE CRITERION OF MINIMUM WORK CYCLE TIME - Khankelov T. K.; Mukhamedova N. B.; ashidov B. U.; Niyazov A. A. (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the formation of a dependency for calculating the operating cycle time of a garbage truck as an optimization criterion and the determination of the main rational parameters of a garbage truck depending on operating conditions in the presence of an optimum objective function. The choice of a rational solution is based on single-criterion optimization based on the analysis of one criterion - the duration of the garbage truck’s working cycle. By differentiating the duration of the garbage truck cycle to perform work operations by the mass capacity of the garbage truck container, the optimal mass of the garbage truck container is determined.